Virtuelles Prototyping einer Robotersteuerung durch interaktive 3D-Simulation - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang

Visual Specification, Modeling, and Illustrations of Complex Systems - Geiger, Christian; Lehrenfeld, G.; Müller, Wolfgang (Proceedings of HICSS-32)
This article introduces and discusses different innovative means for visual specification and animation of complex concurrent systems. It introduces the completely visual programming language Pictorial Janus (PJ) and its application in the customer-oriented design process. PJ implements a completely visual programming language with inherent animation facilities. The article outlines the transformation of purely visual PJ programs into textual imperative programming languages. The second part of the article investigates animated 3D-presentations and introduces a novel approach to an animated 3D programming language for interactive customer-oriented illustrations.
Keywords: Animation; Computer languages; Object oriented modeling; Collaboration; Process design; Graphical user interfaces; Jacobian matrices; Standardization; Feedback; Software prototyping

Scalable System for 3D Audio Raytracing - Müller, Wolfgang; Ullmann, F. (Proceedings IEEE International Conference on Multimedia Computing and Systems)
Though several approaches in sound processing are denoted as 3D audio very few of them generate high quality 3D audio information which allows listeners to exactly locate sound sources in three dimensional space. We present an approach to enhance sound by high quality 3D audio information through acoustic ray tracing where 3D audio is offline processed with digital filters of a head-related transfer function. The basic approach computes a fixed sound source for fixed listener. This approach is extended to generate 3D audio for moving listeners in interactive environments.
Keywords: Ray tracing; Loudspeakers; Motion pictures; Acoustic reflection; Ear; Digital filters; Parallel processing; Humans; Physics; Crosstalk

Relation of fibre intake to HbA1c and the prevalence of severe ketoacidosis and severe hypoglycaemia. EURODIAB IDDM Complications Study Group. - Buyken, Anette; Toeller, M; Heitkamp, G; Vitelli, F; Stehle, P; Scherbaum, WA; Fuller, JH (Diabetologia)

An Example of Task Oriented Empirical Evaluations of 3D-Display Modes - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Journal of Universal Computer Science)

Beller, Walter, “Logic in Mexico”, In: Santiago Ramirez (ed.), Mexican Studies in the History and Philosophy of Science, Kluwer: Dordrecht 1995 (= Boston Stud. Philos. Sci.; 172), 1–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Berufsorientierung in Zeiten der Krise: Thematisierung - Dethematisierung. - Bigga, Regine (Schule und Arbeitswelt. Zwischen Thematisierung und De-Thematisierung von Geschlecht.)

Anregungen für die Lehrplanarbeit hinsichtlich der Gleichstellung der Geschlechter. Lehrpläne für Mädchen und Jungen. - Bigga, Regine (Lisa-Jahrbuch)

Authoring Communicating Agents in Virtual Environments - Geiger, Christian; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the Annual Conference for the Computer Human Interaction)
3D-graphics popularity has steadily increased in a number of areas such as entertainment, scienti c vi- sualization, simulation, and virtual reality. Despite this rapid growth the authoring of animated 3D objects in virtual environments is stil l by no means trivial. This article presents new concepts of the animated 3D programming language SAM (Solid Agents in Motion) and its programming environment. In SAM, the main syntactic objects like agents, rules, and messages are represented as 3D objects. The design of a SAM pro- gram is supported by a dedicated 3D structure editor. The editor al lows the de nition and spatial arrange- ment of SAM agents in a 3D scene by direct manipu- lation. The paper gives a number of SAM examples, demonstrating the authoring of simple animated vir- tual 3D scenarios.

SAM - An Animated 3D Programming Language - Geiger, Christian; Müller, Wolfgang; Rosenbach, W. (Proceedings of the IEEE Symposium on Visual Languages)
This article presents the animated visual 3D programming language SAM (Solid Agents in Motion) for parallel systems specification and animation. A SAM program is a set of interacting agents synchronously exchanging messages. The agent's behaviour is specified by means of production rules with a condition and a sequence of actions each. Actions are linearly ordered and execute when matching a rule. In SAM, main syntactic objects like agents, rules, and messages are 3D. These objects can have an abstract and a concrete, solid 3D presentation. While the abstract representation is for programming and debugging, the concrete representation is for animated 3D end-user presentations. After outlining the concepts of SAM this article gives two programming examples of 3D micro worlds and an overview of the programming environment.
Keywords: Animation; Computer languages; Solids; Concrete; Application software; Virtual reality; Programming profession; Switches; Visualization; Debugging